The lingering menace: How legacy organochlorine pesticides still threaten our rivers and food chains - Wenping Xie; Guangjun Wang; Ermeng Yu; Jun Xie; Wangbao Gong; Zhifei Li; Kai Zhang; Yun Xia; Jingjing Tian; Hongyan Li (Ecotoxicology and Environmental Safety)
The bioaccumulation of organochlorine pesticides (OCPs) in aquatic organisms has been extensively explored in recent years due to associated ecological risks and potential threats to human health through food. This study aims to assess the bioaccumulation of organochlorine pesticides (OCPs) in 18 freshwater fish species from the Pearl River Delta, China. The observed OCP concentrations ranged from 0.69 to 43.15 ng/g wet weight, indicating low to moderate pollution levels. A linear mixed-effects model revealed the contribution of the feeding habits and geographic distributions at 58.67 and 0.67 % of OCP accumulation, respectively. Bottom-dwelling carnivorous fish species exhibited greater OCP residue levels than those in the upper layers of the freshwater. Estuarine organisms showed higher Dichlorodiphenyltrichloroethane (DDT) residue levels than those inland species. On the other hand, although there were no direct carcinogenic or exposure risks associated with OCPs in the study area, potential related hazards were observed. Consumers are, therefore, advised to select fish species from the middle and upper delta rather than bottom fish, shellfish, and shrimp. The current research provides valuable guidance for aquatic food consumption.